Canadian International Petroleum Conference 2004
DOI: 10.2118/2004-170
|View full text |Cite
|
Sign up to set email alerts
|

A New Method of Formulating Finite Difference Equations -Some Reservoir Simulation Examples

Abstract: Finite difference approximations to partial derivatives are generally based on Taylor series, which are polynomial expressions for the unknown variable as a function of the grid locations. In many problems, approximate analytical solutions are known that incorporate the physics of the process. It is proposed that such expressions be used to derive finite difference equations. Increased accuracy is anticipated, particularly when the solutions are highly non-linear, singular, or discontinuous.Reservoir simulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2004
2004
2005
2005

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 5 publications
1
7
0
Order By: Relevance
“…extends the work of Weber et al 27 Weber demonstrated accuracies for the pressure solution normally requiring millions of cells using traditional finite-difference equations with only hundreds of cells. This was accomplished through the use of finite-difference equations that incorporate the physics of the flow.…”
supporting
confidence: 54%
See 1 more Smart Citation
“…extends the work of Weber et al 27 Weber demonstrated accuracies for the pressure solution normally requiring millions of cells using traditional finite-difference equations with only hundreds of cells. This was accomplished through the use of finite-difference equations that incorporate the physics of the flow.…”
supporting
confidence: 54%
“…The new pressure-solution method developed in this thesis is based on the work of Weber et al 27 They proposed that finite-difference equations, used to represent the pressure equation, be based on mathematical expressions that incorporate the physics of the process instead of on traditional polynomial expressions. In modeling reservoir pressures, equations incorporating the physically realistic ln(r) dependence on pressure for reservoirs with straight line wells, and a 1/r dependence for reservoirs with more complex well geometries were used (r is the distance to the wells).…”
Section: Weber's Equations and Nested-grid Descriptionmentioning
confidence: 99%
“…These results are intuitively satisfying, but may be surprising to anyone who has simulated with such a course grid using a traditional reservoir simulator. The precision of the circular saturation contours, as well as the smoothness of the stereamlines, results from the new Weber 13 finite difference equations that include ln(r)-terms in their formulation. Figure 4 shows that the dynamic grid solution for saturation on the stream lines provides a sharp flood front.…”
Section: Two-dimensional Prototype Simulator Resultsmentioning
confidence: 99%
“…Details of the derivation can be found in Weber et al 13 , who show several orders of magnitude improvement in the error in calculated pressures. A pressure drop proportional to ln(r) occurs around infinite, straight-line sources and sinks.…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation